Association between composite dietary antioxidant index and cognitive function impairment among the US older adults: a cross-sectional study based on the NHANES 2011–2014 - Zhao, Cong; Pu, Meng; Wu, Chengji; Ding, Jiaqi; Guo, Jun; Zhang, Guangyun (Frontiers in Nutrition, 2024)
BACKGROUND: Cognitive function impairment (CFI) and the Composite Dietary Antioxidant Index (CDAI) were investigated in this study. METHODS: Participants from the 2011-2014 cycles of the National Health and Nutrition Examination Survey were chosen to assess cognitive function using the Consortium to Establish a Registry for Alzheimer's Disease Word Learning Test, the Animal Fluency Test, and the Digit Symbol Substitution Test. Participants scored below the 25% percentile of any of the three tests were defined as having cognitive function impairment. 24-hour recalls of diet were collected to calculate CDAI. RESULTS: 2424 participants were included. The fully adjusted multivariate logistic regression model showed an increase of one CDAI unit reduced CFI risk by 5% (95% CI: 0.92~0.98, p=0.004). When comparing individuals with the lowest CDAI inthe first quartile (<-2.42), the adjusted odds ratio for CDAI and CFI were 0.81 (95% CI: 0.61~1.06, p=0.125) in the second quartile, 0.69 (95% CI: 0.51~0.92, p=0.012) in the third quartile, and 0.59 (95% CI: 0.43~0.82, p=0.002) in the fourth quartile, respectively. Restricted cubic spline analysis revealed a steady negative linear correlation between CDAI and CFI, with a p-value for non-linearity of 0.122. Subgroup analysis did not reveal any significant interactions based on age, education level, family income, history of diabetes, hypertension, stroke, and depression. CONCLUSION: CDAI was inversely associated with CFI in a large representative American population. Further longitudinal studies are needed for causal inference.